1999
DOI: 10.1111/j.174-1617.1999.tb01307.x
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Distress in Children of High‐conflict Divorce

Abstract: This study examines factors that contribute to the emotional distress of children whose parents experience an acrimonious divorce with conflict over custody and visitation issues. Information was gathered systematically from guardian ad litem reports on 105 children in order to explore the child's emotional distress in response to individual‐, parental‐, marital‐, and custody–related factors. Findings emphasize the impact of the level of marital conflict in predicting increases in the child's emotional distres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0
4

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(27 citation statements)
references
References 21 publications
2
21
0
4
Order By: Relevance
“…She also found that when children remain in high-conflict marital situations, they display lower levels of wellbeing than children whose parents divorce or separate following high conflict. Ayoub, Deutsch and Maraganore (1999) confirm that, though children in high-conflict divorce fare poorer than children in intact families, poor child wellbeing is linked with family conflict in both intact and divorced families.…”
Section: Self-concept Development Experiencessupporting
confidence: 60%
“…She also found that when children remain in high-conflict marital situations, they display lower levels of wellbeing than children whose parents divorce or separate following high conflict. Ayoub, Deutsch and Maraganore (1999) confirm that, though children in high-conflict divorce fare poorer than children in intact families, poor child wellbeing is linked with family conflict in both intact and divorced families.…”
Section: Self-concept Development Experiencessupporting
confidence: 60%
“…Indices of poor adjustment include overall behavior problems as reported by both the parent and child; low self-esteem, acting out as reported by both the child and parent; antisocial behaviors and headstrong behavior as reported by the child; and anxiety/depression as reported by the child. These results are congruent with earlier studies that demonstrated a strong relationship between child maladjustment and co-parenting marked by high hostility and poor parenting skills (Amato & Keith, 1991;Ayoub, Deutsch, & Maraganore, 1999;Demo & Acock, 1988;Hetherington et al, 1982Hetherington et al, , 1985Simons et al, 1999;Vandewater & Lansford, 1998).…”
Section: Discussionsupporting
confidence: 91%
“…Children involved in dependency court hearings were anxious about their appearances and harbored negative attitudes toward their case involvement (Quas et al, 2009). Guardians ad litem in another study reported that children whose parents experienced an acrimonious divorce involving conflict over custody and visitation were extremely emotionally distressed by the process (Ayoub, Deutsch, & Maraganore, 1999). Finally, deficits in children’s understanding of legal terminology, roles, and processes are not exclusively limited to criminal proceedings.…”
Section: Discussionmentioning
confidence: 99%